The impact of big data analytics capability on green supply chain integration: an organizational information processing theory perspective - Shi, Haiqing; Feng, Taiwen; Zhu, Zhanguo (Business process management journal, 2023)
PurposeDespite big data analytics capability (BDAC) has received extensive attention, how and under what conditions BDAC influences green supply chain integration (GSCI) remains unclear. This study draws on organizational information processing theory to examine the mediating effect of supply chain visibility in the BDAC–GSCI link and the moderating effects of flexibility- and control-oriented culture.Design/methodology/approachThe authors examined the research model using two-waved survey data gathered from 317 Chinese firms. The authors employed hierarchical regression analysis and bootstrapping method to test hypotheses and assessed the robust of theoretical model using structural model.FindingsThe authors found that BDAC facilitates all three dimensions of GSCI. Supply visibility mediates the relationship between BDAC and all three dimensions of GSCI, whereas demand visibility only mediates the positive effects of BDAC on green internal and customer integration. In addition, control-oriented culture strengthens the positive impacts of BDAC on supply and demand visibility, while the moderating effects of flexibility-oriented culture are insignificant.Originality/valueThis research contributes to opening the “black box” of how BDAC affects GSCI and provides novel guidelines for firms enhancing the degree of GSCI.